INDONESIA STRATEGY IN SOLVING THE FLIGHT INFORMATION REGION WITH SINGAPORE DURING THE REIGN OF PRESIDENT JOKO WIDODO IN 2014-2019 - Rizky Kurnia Illahi; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research tries to explain how the strategy and diplomacy conducted by Indonesia in resolving the Flight Information Region dispute in the Riau Island Province from Singapore. control of the flight information region which has been controlled by Singapore for a long time, which could harm National interests for a sovereign state of course air space is very important to protect the security and sovereignty of a country, so it is feared that it could disturb stability in the region and impact interests of Indonesia. This research uses the perspective of Neorealism, Neoralism moraemphasis on cooperation and the role of institution -  both government and non-government institutions in international relations. To bridge the problem with the hypothesis This research uses uses foreign policy theory, the level of nation-state analysis and the concept of national security. This research shows that Singapore control Indonesia sky was established at the ICAO convention in Dublin, Ireland, from March 1946 to the present. Indonesia has tried several solutions against Singapore and involved international organizations such as ICAO, but this has not been effective. The influence of Singapore FIR in Indonesia sovereignty and security can be seen from Indonesia airspace in The Riau Island which is a strategic airspace and is located in the Malacca Strait route. Therefore, Indonesia insists on trying to resolve this dispute so that it does not drag on and has a bad impact on the region and Indonesia own interests, this can be seen in the diplomacy carried out by Indonesia and producing a Framework for Negotiation of FIR Realignment, which was signed on 12 September 2019. Keyword : FIR, Dispute, Sovereignty, Security